Modeling dark matter halos with nonlinear field theories - Correa, R. A. C.; Moraes, P. H. R. S.; Dutra, A. de Souza [UNESP]; Dors, O. L.; Paulai, W. de; Frederico, T. (Amer Physical Soc, 2021)
In the present work, we adopt a nonlinear scalar field theory coupled to the gravity sector to model galactic dark matter. We find analytical solutions for the scalar field considering the weak field gravity limit, which is usually done in galaxy rotation curves analysis and in order to do so we assume an isotropic spacetime and a field potential, with a position dependent form of the superpotential, which entails the nonlinear dynamics of the model with self-interactions. The model introduces a position dependent enhancement of the self-interaction of the scalar fields toward the galaxy center, and while going toward the galaxy border the interaction tends to vanish building a non-self-interacting DM scenario. The developed approach is able to provide a reasonable analytical description of the rotation curves in both dwarf and low surface brightness late-type galaxies, with parameters associated with the dynamics of the scalar field.